Environmental virus detection associated with asymptomatic SARS-CoV-2-infected individuals with positive anal swabs - Huang, Ying (Sci Total Environ, 2021)
In the fight against the outbreak of COVID-19 in China, we treated some asymptomatic infected individuals. This study aimed to detect pathogens in biological and environmental samples of these asymptomatic infected individuals and analyse their association. Using a cross-sectional study design, we collected biological and environmental samples from 19 patients treated in the isolation ward of Nanjing No.2 Hospital. Biological samples included saliva, pharyngeal swabs, blood, anal swabs, and exhaled breath condensate. Swab samples from the ward environment included inside masks, outside masks, palm swabs, bedside handrails, bedside tables, cell phone screens, toilet cell phone shelves, toilet pads and toilet lids. We also obtained some samples from public areas. We used RT-PCR to detect pathogens and colloidal gold to detect antibodies. As results, 19 asymptomatic infected individuals participated in the survey, with 8 positives for pathogens and 11 positives only for antibodies. Three positive samples were detected from among 96 environmental samples, respectively, from a cell phone surface, a cell phone shelf and a bedside handrail. No positive samples were detected in the exhaled breath condensate in this work. All patients identified pathogens in the environment had positive anal swabs. There was a statistical association between positive anal swabs and positive environmental samples. The association of positive samples from the surrounding of asymptomatically infected patients with positive anal swabs suggested that patients might secrete the virus for a more extended period.